P345 HEALTH LITERACY AS A MEASURE OF NURSING COMPLEXITY OF CARE IN A DEPARTMENT OF CARDIOVASCULAR MEDICINE. (18th May 2022) - De Rinaldis, M; Cristofori, E; Iula, A; Conte, M; Cocchieri, A
Abstract: Background: HL plays a fundamental role in patients' healthcare. According to the American Medical Association, HL can be viewed as a stronger predictor of a person's health status than age, education level, and race. HL concept has many implications for nursing; they are responsible for identifying the patient's barriers to their health information's comprehension and providing specific nursing interventions in minimizing barriers. Moreover, HL assessment is necessary to plan tailored interventions, improve their efficacy through patient–centered communication. As a part of the nursing process, the nursing diagnosis (ND) classifies patients according to their level of nursing dependency and can be predictive for the nursing workload. No studies have been conducted on the relationship between NDs and HL. We aimed to describe the prevalence and distribution of NDs on admission in patients with CDs and to analyze the relationship between HL and NDs. Method: A retrospective design was used to randomly select 134 patients with CDs in eight cardiovascular and internal medicine units of an Italian hospital from 10 January to 10 May 2021. NDs were collected using a nursing information system (NIS). Single Item Literacy Screener (SILS) was used to measure HL and was systematically reported on NIS. Results: A mean of 3.5 ± 2.3 nursing diagnosis per patient was identified. A statistically significant linear association (Spearman's correlation coefficient) was observed between HL score and the number of NDs. Conclusion: HL was associated with the number of NDs.